Bridging the gap between DeafBlind minds: interactional and social foundations of intention attribution in the Seattle DeafBlind community - Edwards, Terra (Frontiers in Psychology, 2015)
This article is concerned with social and interactional processes that simplify pragmatic acts of intention attribution. The empirical focus is a series of interactions among DeafBlind people in Seattle, Washington, where pointing signs are used to individuate objects of reference in the immediate environment. Most members of this community are born deaf and slowly become blind. They come to Seattle using Visual American Sign Language, which has emerged and developed in a field organized around visual modes of access. As vision deteriorates, however, links between deictic signs (such as pointing) and the present, remembered, or imagined environment erode in idiosyncratic ways across the community of language-users, and as a result, it becomes increasingly difficult for participants to converge on objects of reference. In the past, DeafBlind people addressed this problem by relying on sighted interpreters. Under the influence of the recent “pro-tactile” movement, they have turned instead to one another to find new solutions to these referential problems. Drawing on analyses of 120 h of videorecorded interaction and language-use, detailed fieldnotes collected during 12 months of sustained anthropological fieldwork, and more than 15 years of involvement in this community in a range of capacities, I argue that DeafBlind people are generating new and reciprocal modes of access to their environment, and this process is aligning language with context in novel ways. I discuss two mechanisms that can account for this process: embedding in the social field and deictic integration. I argue that together, these social and interactional processes yield a deictic system set to retrieve a restricted range of values from the extra-linguistic context, thereby attenuating the cognitive demands of intention attribution and narrowing the gap between DeafBlind minds.